Analisis Terhadap Kontrak Ijarah dalam Praktik Perbankan Syariah - Diky Faqih Maulana (IAIN Ponorogo, 2021)
AbstractPeople who need funds can use financing services provided by Islamic financial institutions, one of which is ijarah financing. The provisions of ijarah have certainly been regulated, both theoretically and practically. However, have Islamic financial institutions implemented ijarah contract practices in accordance with existing regulations? Moreover, the clause in the contract, is each contract clause in accordance with the provisions of the ijarah contract and in accordance with Islamic principles? The results showed that the Ijarah Agreement Benefit Lease Financing Agreement Number:10669/IJR/IX/2012 as a whole is in accordance with the provisions of the DSN-MUI fatwa No.09/DSN-MUI/IV/2000 regarding ijarah financing. However, there are some clauses that do not pay attention to the principles of the contract in Islamic law such as the principle of balance (mabda 'at-tawazun fi al-mua'wadah) and the principle of benefit (not burdensome). But apart from that, this contract is in accordance with the DSN Fatwa No.43/DSN-MU/VIII/2004 regarding Compensation (Ta'widh) and Fatwa DSN No.17/DSN-MUI/IX/2000 regarding Sanctions for Customers who Delay Payment. In dispute resolution also uses the concept of al-sulh (peace) recommended in Islam, as the Word of Allah in QS Al Hujurat verse 10. As well as fulfilling the principle of freedom of contract (mabda 'hurriyyat at-ta'aqud) which still pays attention to Islamic moral principles and order general syar'i in contracting. AbstrakMasyarakat yang membutuhkan dana bisa menggunakan jasa pembiayaan yang disediakan oleh lembaga keuangan syariah, salah satunya pembiayaan ijarah. Ketentuan ijarah tentunya telah diatur, baik secara teori maupun praktik. Akan tetapi, apakah lembaga keuangan syariah telah menerapkan praktik akad ijarah sesuai dengan ketentuan yang ada? Terlebih klausul dalam kontrak, apakah setiap klausul kontrak telah sesuai dengan ketentuan akad ijarah serta sesuai dengan prinsip Islam? Hasil penelitian menunjukkan bahwa, Perjanjian Pembiayaan Sewa Manfaat Akad Ijarah Nomor:10669/IJR/IX/2012 secara keseluruhan telah sesuai dengan ketentuan fatwa DSN-MUI No.09/DSN-MUI/IV/2000 tentang pembiayaan ijarah. Namun ada beberapa klausul yang kurang memperhatikan asas akad dalam hukum Islam seperti asas keseimbangan (mabda’ at-tawazun fi al-mua’wadah) dan asas kemaslahatan (tidak memberatkan). Namun diluar hal itu, kontrak ini telah sesuai dengan Fatwa DSN No. 43/DSN-MUI/VIII/2004 mengenai Ganti Rugi (Ta'widh) dan Fatwa DSN No.17/DSN-MUI/IX/2000 mengenai Sanksi atas Nasabah yang Menunda-nunda Pembayaran. Pada penyelesaian sengketa juga menggunakan konsep al-sulh (perdamaian) yang dianjurkan dalam Islam, sebagaimana Firman Allah dalam Q.S Al Hujurat ayat 10. Serta memenuhi asas kebebasan berkontrak (mabda’ hurriyyat at-ta’aqud) yang tetap memperhatikan kaidah akhlak Islam dan ketertiban umum syar’i dalam berkontrak.